Republic of Korea : 2011 Article IV Consultation: Staff Report and Public Information Notice on the Executive Board Discussion. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2011)
Korea's rapid recovery from the global downturn has transitioned into a full-fledged expansion. Policies to strengthen the resilience of the economy and pave the way for sustained and equitable growth is required. Greater two-way flexibility of the exchange rate is needed to support the monetary policy response to inflation and help alleviate capital inflow pressures. Enhancing the overall macroeconomic and financial policy framework will bolster the resilience of the economy to shocks. Housing policies in the macrofinancial framework will contain leverage and prevent asset price bubbles.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet